2007
DOI: 10.1002/hec.1239
|View full text |Cite
|
Sign up to set email alerts
|

The role of private providers in treating child diarrhoea in Latin America

Abstract: Diarrhoeal disease, a leading cause of child mortality, disproportionately affects children in low-income countries - where private and non-governmental providers are often an important source of health care. We use 10 Living Standards Measurement Surveys from Latin America to model the choice of care for child diarrhoea in the private sector compared to the public sector. A total of 36.8% of children in the combined data set saw a private provider rather than a public one when taken for treatment. Each additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 20 publications
1
12
0
1
Order By: Relevance
“…Contrary to prior work, we mitigated doubts that these results may be driven by other factors because we controlled for key confounders. [20][21][22] We found that controlling for confounders reduced estimates on the public-private discrepancy, but the adjusted effect of 15.1% points was still sizable and significant. Juxtaposing these results with the portion of children that received care in the private sector (24%) and the portion of children that were not treated with ORT in our sample (33.2%) implies that eliminating the publicprivate difference in ORT provision would decrease the portion of children not receiving ORT by 3.7% points (0.24 + 0.151 = 0.037).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Contrary to prior work, we mitigated doubts that these results may be driven by other factors because we controlled for key confounders. [20][21][22] We found that controlling for confounders reduced estimates on the public-private discrepancy, but the adjusted effect of 15.1% points was still sizable and significant. Juxtaposing these results with the portion of children that received care in the private sector (24%) and the portion of children that were not treated with ORT in our sample (33.2%) implies that eliminating the publicprivate difference in ORT provision would decrease the portion of children not receiving ORT by 3.7% points (0.24 + 0.151 = 0.037).…”
Section: Discussionmentioning
confidence: 89%
“…For example, most pharmacies are privately owned and have been shown to have low ORS provision rates relative to other facility types. 19,22 We controlled for geographic confounders by including a rural/urban indicator variable (defined by the DHS administrators) and a set of dummy variables for each region within a country for each year. Finally, we controlled for secular trends by including a set of dummy variables for each survey year.…”
Section: Methodsmentioning
confidence: 99%
“…Studies also show evidence of over-medication and over-treatment in the private sector. Waters et al (2008) used the Living Standard Measurement Surveys of 10 Latin American countries (LACs) and found that children treated by a private provider were more likely to receive more drugs, most commonly unnecessary antibiotics. This treatment was of lower quality and less effective than the care provided by the public sector.…”
Section: Introductionmentioning
confidence: 99%
“…It already accounts for the majority of total health care expenditures, mainly as a result of poor public sector coverage. For instance, private physicians account for 38% of the treatment of children in rural Guatemala (Van der Stuyft et al, 1996;Waters et al, 2008), and throughout LAC most of the private expenditure on health care comes from out-of-pocket payments. Private and non-governmental providers have become an important source of health care, but there is still little documentation on the extent and nature of such providers, especially in relation to their role as providers of preventive and public health interventions.…”
Section: Introductionmentioning
confidence: 99%
“…Most children currently obtain some form of treatment for diarrhoea, but most of them receive inappropriate treatments such as antibiotics and antidiarrhoeal agents. 11 Merely switching the treatments children receive, which is less challenging than trying to change caregivers' treatment seeking behaviour, could therefore drive substantial increases in ORS and zinc coverage.…”
mentioning
confidence: 99%